La cooperación internacional descentralizada para el desarrollo en México - Velázquez Flores , Rafael; Schiavon, Jorge A. (Revista Española de Desarrollo y Cooperación, 2023)
The central objective of this article is to analyze the actions of decentralized international cooperation for development (DICfD) conducted by Mexican local governments, both at the state and municipal levels. The first section describes the concept of DICfD based on the Mexican experience. The second part presents the international and domestic variables which explain the increase in these types of actions. The third analyzes the legal framework under which Mexican local governments conduct DICfD. Finally, the last section describes the types and forms of international participation of Mexican local governments within the framework of DICfD.